2015
DOI: 10.1111/epi.13223
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam augments short‐term depression and slows vesicle recycling

Abstract: SUMMARYObjective: Brivaracetam (BRV) decreases seizure activity in a number of epilepsy models and binds to the synaptic vesicle glycoprotein 2A (SV2A) with a higher affinity than the antiepileptic drug levetiracetam (LEV). Experiments were performed to determine if BRV acted similarly to LEV to induce or augment short-term depression (STD) under high-frequency neuronal stimulation and slow synaptic vesicle recycling. Methods: Electrophysiologic field excitatory postsynaptic potential (fEPSP) recordings were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…1 However, BRV displays a 15-30-fold higher affinity than LEV in binding to the native or recombinant SV2A protein 3 and was recently reported to also reveal a differential interaction to SV2A from LEV. 4 This correlates with previous findings showing BRV to possess a different pharmacological profile from LEV in preclinical seizure and epilepsy models consisting of both more potent and more complete seizure suppression. 4 This correlates with previous findings showing BRV to possess a different pharmacological profile from LEV in preclinical seizure and epilepsy models consisting of both more potent and more complete seizure suppression.…”
supporting
confidence: 90%
“…1 However, BRV displays a 15-30-fold higher affinity than LEV in binding to the native or recombinant SV2A protein 3 and was recently reported to also reveal a differential interaction to SV2A from LEV. 4 This correlates with previous findings showing BRV to possess a different pharmacological profile from LEV in preclinical seizure and epilepsy models consisting of both more potent and more complete seizure suppression. 4 This correlates with previous findings showing BRV to possess a different pharmacological profile from LEV in preclinical seizure and epilepsy models consisting of both more potent and more complete seizure suppression.…”
supporting
confidence: 90%
“…This effect may be explained by its specific binding to the presynaptic vesicle protein SV2A. This protein is expressed on excitatory and inhibitory neurons throughout the central nervous system (Klein et al, ), but BRV may exert its antiepileptic effects predominantly through depression of excitatory neurotransmission (Yang et al, ).The current BRV findings are in agreement with previous TMS‐EMG studies that reported a depression of MEP input–output curves under levetiracetam (Reis et al, ; Sohn, Kaelin‐Lang, Jung, & Hallett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments with an SV2A allosteric modulator demonstrated that brivaracetam's interaction with SV2A differs from that of levetiracetam, likely inducing or stabilizing different SV2A protein conformations . This probably explains findings from electrophysiologic studies in rat hippocampal slices showing a superior ability of brivaracetam to inhibit synaptic transmission and vesicle release, which correlates with its distinct pharmacodynamic properties …”
Section: Brivaracetammentioning
confidence: 99%